Reading on Nausea and The Immoralist Through Existentialism - Wenanda, Diva (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2021)
The concept of existentialism is that the existence of a person is prior to their essence. The term "existence precedes essence" subsequently became a maxim of the existentialist movement. Put simply, this means that there is nothing to dictate that person's character, goals in life, and so on; that only the individual can define their essence. This study discussed existentialism in Nausea by Jean Paul Sartre and The Immoralist by Andre Gide, through Roquentin and Michel as the Characters. Roquentin and Michels, they tend to have an absolute freedom, means there is no influence from outside. What they actually want sometimes lies no motives why they are doing that thing.